Mobiliser la propriété publique en faveur de l’agriculture périurbaine ? Le cas de la région de Montpellier (France) - Coline Perrin (VertigO)
This paper explores the potential role of public properties in the maintenance or redevelopment of urban agriculture. It is based on a spatial analyzis of public properties, public acquisitions and on in-depth interviews in Montpellier city region. The results show that the public properties represent a considerable spatial extent, but less than half of the surfaces has an interest for agriculture due to land fragmentation, the specific features of land or urbanization perspectives. Agriculture remains marginal in public land strategies. Public and parapublic land acquisition and management are rarely coordinated. However, some local authorities develop strategies for farmland protection. Other public bodies turn to agriculture to maintain the land in their possession. They show that public properties could thus become a lever to maintain or redevelop agriculture on the urban fringe.